Implementasi Prinsip Good Environmental Governance (GEG) dalam Pembangunan Permukiman: Studi Kasus Kelurahan Mugirejo Kota Samarinda - Devy Khotimah; Sry Reski Mulka (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the implementation of Good Environmental Governance (GEG) in settlement development in Mugirejo Village, Samarinda City, and its implications for flood vulnerability. The study used a qualitative method with a descriptive approach. Data collection was conducted through interviews, observation, and documentation in Mugirejo Village, Samarinda City. Research informants consisted of officials and staff from the Housing and Settlement Agency, the Environmental Agency, the Regional Development Planning Agency (Bappeda) of Samarinda City, and Mugirejo Village officials involved in settlement and environmental development management. Data analysis was conducted through data condensation, data presentation, and drawing conclusions by referring to the seven GEG principles as an analytical framework. Data validity was tested using source triangulation and technical triangulation. The results of the study indicate that the implementation of GEG in settlement development in Mugirejo Village has not been optimal and is still dominated by an administrative-procedural approach. Weak law enforcement, limited public participation, and institutional fragmentation are the main factors that hinder the effectiveness of environmental governance. These conditions have increased flood vulnerability due to land conversion and uncontrolled settlement expansion. This study recommends strengthening inter-agency coordination, increasing more inclusive public participation, and consistently enforcing environmental regulations to support sustainable and flood-resilient settlement development.